Modulating ultrasound-assisted extraction of polysaccharide-protein complexes from β-glucan-rich medicinal mushrooms for enhanced antioxidant activity - Emily Wan Ting Tam; Yi Ching Cheung; Wesley Chin Ho Lung; Ching Ching Hui; William W.Y. Lam; Stella Siu Mui Ng; Franklin Wang Ngai Chow (Carbohydrate Polymer Technologies and Applications)
The growing nutraceutical interest in polysaccharide-protein complexes (PSPs) from β-glucan-rich medicinal mushrooms necessitates efficient extraction methods. This study examined the impact of various ultrasound-assisted extraction (UAE) parameters, including ultrasound power, temperature, mushroom particle size, and solid-to-liquid ratio, on the composition and antioxidant activities of PSPs extracts from Lentinula edodes (L. edodes) and Grifola frondosa (G. frondosa). Using a Box–Behnken design and response surface methodology, second-order polynomial models were developed to correlate UAE parameters with PSPs antioxidant activity, demonstrating strong model fit with high F-values and low p-values (F-value = 8.64, p-value = 0.0143 for L. edodes; F-value = 42.41, p-value = 0.0003 for G. frondosa). The models showed a high degree of correlation between observed and predicted values, with variations depending on mushroom species. Optimal UAE conditions for achieving the highest antioxidant PSPs were identified for L. edodes (55 °C, 6.21 W/cm² ultrasound power, particle size <600 µm) and G. frondosa (70 °C, 6.21 W/cm² ultrasound power, particle size of 600–850 µm). A higher protein-to-polysaccharide ratio in PSPs was correlated with enhanced antioxidant activity. UAE presents a promising technique for enhancing the antioxidant properties of PSPs in pharmaceutical formulations, potentially broadening their use in extracting bioactive compounds from other medicinal mushrooms to promote health and wellness.